2017
DOI: 10.1016/j.aam.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Congruences and concurrent lines in multi-view geometry

Abstract: We present a new framework for multi-view geometry in computer vision. A camera is a mapping between P 3 and a line congruence. This model, which ignores image planes and measurements, is a natural abstraction of traditional pinhole cameras. It includes two-slit cameras, pushbroom cameras, catadioptric cameras, and many more. We study the concurrent lines variety, which consists of n-tuples of lines in P 3 that intersect at a point. Combining its equations with those of various congruences, we derive constrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 29 publications
(110 reference statements)
3
31
0
Order By: Relevance
“…These results show that the selectivity to faces and places in the FFA and PPA is to some extent determined by the image properties that are preserved by local-scrambling, such as the spatial envelope of the image. This fits with previous studies that have demonstrated selectivity in higherlevel regions of the ventral stream to spatial properties of the image (Bracci & Op de Beeck, 2016;Cichy et al, 2013;Golomb & Kanwisher, 2012;Levy, Hasson, Avidan, Hendler, & Malach, 2001;Ponce, Sturmfels, & Trager, 2017;Watson et al, 2016). More generally, these results are consistent with previous studies that have shown that patterns of response in high-level visual regions are sensitive to image properties (Rice et al, 2014;Watson et al, 2016;Xu, Yue, Lescroart, Biederman, & Kim, 2009;Yue, Tjan, & Biederman, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…These results show that the selectivity to faces and places in the FFA and PPA is to some extent determined by the image properties that are preserved by local-scrambling, such as the spatial envelope of the image. This fits with previous studies that have demonstrated selectivity in higherlevel regions of the ventral stream to spatial properties of the image (Bracci & Op de Beeck, 2016;Cichy et al, 2013;Golomb & Kanwisher, 2012;Levy, Hasson, Avidan, Hendler, & Malach, 2001;Ponce, Sturmfels, & Trager, 2017;Watson et al, 2016). More generally, these results are consistent with previous studies that have shown that patterns of response in high-level visual regions are sensitive to image properties (Rice et al, 2014;Watson et al, 2016;Xu, Yue, Lescroart, Biederman, & Kim, 2009;Yue, Tjan, & Biederman, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Roughly speaking, a multi-view variety parametrizes all the possible images that can be taken by a fixed collection of cameras. See [1,11,14] for more details on multi-view varieties. See [13] for a survey on various camera models.…”
Section: Introductionmentioning
confidence: 99%
“…The work [11] presents a new point of view to study the multi-view varieties. A photographic camera maps a point in the scene to a point in the image.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations